ANALISIS PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 4 SURABAYA - VISTA DECIANA B (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Problems that are often encountered by teachers are less prepared well evaluation tools and impressed carelessly without regard to the achievement indicator of each basic competency. Based on interviews with the teacher partners, in implementing the evaluation without doing the analysis of the test items given in advance. To determine the feasibility of the evaluation tool used by the teacher it is necessary to analyze the use of evaluation tools in economic subjects the accounting materials in class XI IPS SMA Negeri 4 Surabaya. This research is descriptive research that is used to explain and describe the evaluation tool used by teachers and feasibility. Subjects were teachers economic subjects the accounting material class XI IPS SMA Negeri 4 Surabaya. While the object of the study is an evaluation tool. Results of this study are evaluation tools used in class XI IPS is a written test evaluation tool shaped test description. The written test is used to form the test description daily tests because it is more in accordance with the indicators in each basic competence in economic subjects the accounting materials and teachers make tests easier in the form of a written description. Evaluation tool has met the eligibility criteria established Directorate PSMA 2010 of 91.67% (very decent) however there should be efforts to improve. Key words : The use of evaluation tools, form of evaluation tools, feasibility